Vielfältig geprägt. Das spätperserzeitliche Samaria und seine Münzbilder - Wyssmann, Patrick (2019)
The coins from the province of Samaria in the Persian Period and the imagery depicted on them are at the centre of this volume. The corpus, normally referred to as Samarian Coinage, presently consists of approximately 250 coin types; the provenience from Samaria can be established with relative certainty for 165 of these types. Silver coins (drachms, obols, hemiobols, and quarter obols) minted between 401 and 332 BCE, they are characterised by a wide iconographic variety. A comprehensive study of the images on these coins promises important insights into the region’s history and culture. The present monograph provides a detailed iconographic analysis on the basis of a critical study of the numismatic material with reference to numerous comparative items. A new approach to dating the coin minting in Samaria results in a better understanding of the coin imagery, as the division into four minting phases enables a closer examination of each coin issuer’s preferences. The meticulous evaluation of the pictorial sources, interpreted against the historical background of the 4th century BCE, sheds new light on Samaria before the dawn of the Hellenistic Period.